Theodore - Keating, Frank, 1937-; Wimmer, Mike (New York : Simon & Schuster Books for Young Readers, 2006)
A biography of Theodore Roosevelt that imagines the president looking back on his life, describing his childhood, his youthful journeys throughout the world, his experiences as a leader, and the value he placed on knowledge, adventure, originality, and integrity.
"A Paula Wiseman book."
Includes bibliographical references.
2.2
K-3
Keywords: Roosevelt, Theodore, -- 1858-1919 -- Childhood and youth -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Roosevelt, Theodore, -- 1858-1919 -- Childhood and youth; Presidents; Roosevelt, Theodore, -- 1858-1919.; Presidents -- United States -- Biography